Enhanced Photoelectrochemical Response from Copper Antimony Zinc Sulfide Thin Films on Transparent Conducting Electrode - Prashant K. Sarswat; Michael L. Free (International Journal of Photoenergy)
Copper antimony sulfide (CAS) is a relatively new class of sustainable absorber material, utilizing cost effective and abundant elements. Band gap engineered, modified CAS thin films were synthesized using electrodeposition and elevated temperature sulfurization approach. A testing analog of copper zinc antimony sulfide (CZAS) film-electrolyte interface was created in order to evaluate photoelectrochemical performance of the thin film of absorber materials. Eu3+/Eu2+ redox couple was selected for this purpose, based on its relative band offset with copper antimony sulfide. It was observed that zinc has a significant effect on CAS film properties. An enhanced photocurrent was observed for CAS film, modified with zinc addition. A detailed investigation has been carried out by changing stoichiometry, and corresponding surface and optical characterization results have been evaluated. A summary of favorable processing parameters of the films showing enhanced photoelectrochemical response is presented.